Transcriptomic Profiling of the Maize (Zea mays L.) Leaf Response to Abiotic Stresses at the Seedling Stage - Li, Pengcheng; Cao, Wei; Fang, Huimin; Xu, Shuhui; Yin, Shuangyi; Zhang, Yingying; Lin, Dezhou; Wang, Jianan; Chen, Yufei; Xu, Chenwu; Yang, Zefeng (Frontiers in Plant Science, 2017)
Abiotic stresses, including drought, salinity, heat, and cold, negatively affect maize (Zea mays L.) development and productivity. To elucidate the molecular mechanisms of resistance to abiotic stresses in maize, RNA-seq was used for global transcriptome profiling of B73 seedling leaves exposed to drought, salinity, heat, and cold stress. A total of 5,330 differentially expressed genes (DEGs) were detected in differential comparisons between the control and each stressed sample, with 1,661, 2,019, 2,346, and 1,841 DEGs being identified in comparisons of the control with salinity, drought, heat, and cold stress, respectively. Functional annotations of DEGs suggested that the stress response was mediated by pathways involving hormone metabolism and signaling, transcription factors (TFs), very-long-chain fatty acid biosynthesis and lipid signaling, among others. Of the obtained DEGs (5,330), 167 genes are common to these four abiotic stresses, including 10 up-regulated TFs (five ERFs, two NACs, one ARF, one MYB, and one HD-ZIP) and two down-regulated TFs (one b-ZIP and one MYB-related), which suggested that common mechanisms may be initiated in response to different abiotic stresses in maize. This study contributes to a better understanding of the molecular mechanisms of maize leaf responses to abiotic stresses and could be useful for developing maize cultivars resistant to abiotic stresses.